Ris - Ferdinand, Klaus (Kuml, 1959)
Rice - Aspects of Cultivation and Treatment in East Afghanistan The staple of life in Afghanistan is rice, and everyone who by any means can afford it eats some meal based on rice once or twice a day. The country is selfsupporting in the production of rice, the relatively high temperatures necessary during the 4-6 months of growth being available over much of the country, though the plentiful and constant supply of water which is also essential is not so commonly available. Rice is therefore cultivated in patches spread over the country, in particular around the central mountains, where rivers and larger streams make irrigation possible. It is found, for example, near the towns of Herāt and Qandahār at about 1000 metres above sealevel, but also up to 2000 metres in Kābul province; but the really large-scale producing areas are the well-watered plains around Khānābād and Qunduz north of the Hindū Kush, and the Laghmān district in east Afghanistan. It is from here that the greatest quantities come onto the market, and from here that the most prized varieties come. Afghans are very particular about types and qualities of rice. They distinguish two main varieties, ma’īn (mahīn) and lok, which Vavilov has shown to be two botanical varieties, both of which he classes under ordinary rice, Oryza sativa L. Ma’īn, or bārīk (ar.) - both terms meaning thin and fine - is the most prized, and characterized by long trin grains, always very hard and transparent. The grain is about 7 mms. long and its length-breadth ratio is 1: 3--3.5. Lok, on the other band, with its shorter and thicker grains, is less highly prized. Its length seldom exceeds 5.5 mms., and its ratio is 1: 1.6-1.8. It is also more starchy and floury.1). While lok is cultivated throughout Afghanistan, and according to Vavilov resembles in essentials the Turkestan types of rice, ma’īn is derived from India and is confined first and foremost to Laghmān and adjoining areas and to the Qataghan province in the north, particularly around Khānāhād. 2). The following description is based on first-hand experience of the rice-hulling process in Laghmān, supplemented by further material collected from Afghan informants in Kābul and Copenhagen. The Laghmān rice area. In February 1955, my wife and I visited the lowland areas of Afghanistan's eastern province, Mashriqī, now called Nangarhār, of which Jalālābād is the centre. These lowlands, lying 600-900 metres above sea-level, form a warm basin in the highlands of east Afghanistan, in many ways a prelude to the lndus valley. Climatically it is subtropical, with a light rainfall and a natural vegetation consisting of sparse bush-steppe. Agriculture is therefore predominantly based on irrigation; kārēz irrigation exists, for example southeast of Jalālābād, but for heavy crops of rice river irrigation is necessary. The most favourable conditions are undoubtedly found in lower Laghmān, where the rivers 'Alīshang and Alingār run, first separately and then conjoined, through a level river plain, which can he irrigated with the river water without undue trouble. Laghmān is thickly populated; habitations are scattered over the cultivated area (Fig. 1), though some open villages are sited along the edge of the river plain (Fig. 2). The habitations consist partly of isolated qal'a's (lit.: castles) where individual families of large landowners live, partly of qal' a's around which lie the clay houses of the normally landless villagers, and finally of compact towns without any real "castle". The two villages which we came to know well were of the two latter types. The population of Laghmān is today extremely mixed. In earlier days the area was dominated by the lndian-speaking Pashaī, by the east-Iranian speaking Afghan tribe of Sāfī, and probably also by pure Persian-speakers (Tājīks). The area is still bilingual, inasmuch as Pashaī is yielding place to the other two languages. While the surrounding mountain areas have largely retained their former character the lowlands are changing rapidly, and there is scarcely an Afghan tribe which cannot now be found here. The result is that the tribes no longer cover a definite district, and the tribal organisation is, in my opinion, broken and replaced by village units, led by individual families, often closely connected with Kābul. A sort of feudalism has resulted. Thus we find in some villages that the landowners are Afghans, while the subordinate farmers are of many different Afghan tribes, most often Tājīks (among whom the Pashaī are normally included). In the villages there are in addition a number of craftsmen, carpenters, smiths, weavers, barbers, pottery-makers, leather-workers, etc., who to a degree lie outside the normal groupings of Afghans and Tājīks, and are regarded as belonging to separate qaums, a term which really means "tribes", but is best here translated as craft castes. This widespread division into hereditary craft castes, some of which are looked down upon, is particularly prevalent in eastern Afghanistan, and may doubtless be regarded as a transitional stage to the position in western India. Among these craft castes is one whose particular work is the husking of rice. This "tribe", the Hussain Khēl, lives in the villages as hamsāya, a type of inferior guests. Their origin is unknown. As I recall, they believe themselves to belong to the Afghan tribe of Mohmand, but this is not generally accepted by the villagers, and they are probably of lndian origin. The work of the Hussain Khēl takes place in winter, after paddy or hulled rice (p. shālī) has been threshed by being trodden out by oxen or donkeys (Fig. 3). There are three stages: boiling, shock-drying and finally hulling in a stamp-mill. The process, described below, involves ma’īn, though lok (af.: ghati) also exists here. Treatment and hulling of ma’īn-rice. In the Laghmān villages we saw rows of pottery jars in the various stages of paddy-boiling (cf. Figs. 4 and 5). We were told that it was usual for the paddy just to be brought to the boil, and then allowed to simmer for a whole night. The next morning the jars were inverted to allow the water to run off, and shortly afterwards the damp paddy was ready for drying by being mixed with redhot sand. This look place by a beehive-shaped clay lined oven, about 2.5 metres high, (cf. Figs. 6 and 7) with two openings in the side, a smaller (Figs. 6 and 7, right) where a young man threw rice hulls on the fire and, in the intervals, provided a strong draught with a plaited fan, and a larger opening from which hot sand was removed with a little iron spade. The sand was poured upon dark yellow damp paddy in a large flat wooden bowl (Fig. 8), and the sand and paddy were mixed together for a few moments, before the steaming mass was emptied onto a large sieve, and the sand sieved away with a rolling action. The dry, light yellow paddy is now ready to go to the stamp-mill. In Laghmān, with its plentiful water, hulling is normally carried out in a double-armed water-driven stamp-mill (cf. Figs. 10-12). Experience is needed, to avoid breaking too many grains, and the pestles must on no account hit the bottom of the mortar. The interior of the mortars is therefore made fairly deep and narrowing towards the bottom. Despite that, we saw in Laghmān that some of the paddy sprang up from the mortars at every stroke, and that a man had continuously to push it back. The process is said to be the same in Wardak, an important lok-rice area between Kābul and Ghaznī, and there, as probably in Laghmān, the pointed-hollow mortars are made of wood. In Lōgar the mortar hollow is deep and lined with wood, with one vertical and one sloping side (cf. Fig. 12), ensuring that the paddy is not pushed out but is turned at each stroke. To protect the paddy further the end of the pestle is hollowed and banded with iron, so that it keeps its shape. The quantity hulled at a time varies according to the type of mortar. In Wardak it is possible to have twice 12 sēr, or about 168 kilos (1 sēr = about 7 kilos), in a single filling, while in Lōgar not more than twice 4 sēr, or about 56 kilos, are hulled at a time. The hulling may take several hours, depending on the hardness of the paddy, and gradually more and more dust and hulls collect on top of the rice. This the miller takes as his due. He stops the stamp-mill by throwing a loop of rope (fastened to the ground) around one of the pestle arms, the dustcovered rice is taken up, and, while it is being cleaned, new paddy is put below the pestle. The cleaning is sometimes done by a particular wandering people, the Musalī. First, special wooden shovels (p.: rāshbēl) are used to seperate the hulls from the rice, and then the dust is removed from the completely hulled rice in special winnowing trays (p.: chaj or chach). When all the rice has been hulled it is sorted by size, by sieving through up to three different sieves (p. cheghæl). The Hussain Khēl has now finished his treatment of the rice, and it is returned to the owner, who receives 44 sēr of cleaned rice (p.: berini) for every 80 sēr of paddy which he has sent for hung. The remainder, about 7 sēr of rice, forms the payment to the Hussain Khēl. If the paddy is particularly dry their payment can rise to about 10-12 sēr. Thus prepared the rice goes onto the market. But before it is used as food it must be washed thoroughly, and soak for 2-3 hours, as the grain is very hard,. This treatment of paddy, characterized by parboiling and quick drying, is clearly only used with the ma’īn or bārīk variety of rice, as other informants confirm. Thus 'Abdul 'Azīz Sultanī, from the Lōgar valley (cf. p. 225) where admittedly only the lok variety is cultivated, could give the following description of the treatment of ma’īn: The threshed paddy is boiled, from 2-3 hours up to a day and a night, depending on which of eight varieties of ma’īn was being treated. It is then dried in the sun, or mixed with hot sand and then sieved through a wire sieve. Sultanī was unable to localise the two methods, and it should be recorded that he disagreed strongly with my terming the mixing with sand a drying process; he said that it was a "roasting" (p.: berīām kardan), and compared it with still another method, whereby the damp paddy is placed on a very hot iron plate "just as maize is made into popcorn". In fact the treatment of ma’īn seems to show a large variety of minor variations within an essentially uniform process. I have information from Khānābād, in the Qataghan province of north Afghanistan, an area originally inhabited predominantly by Uzbeks, but today a mixed area as during the last decades many Afghans have been granted land there. My information was collected in Kābul, and I do not know whether it concerns ma’īn or lok, though I consider the former most likely. In Khānābād the treatment of rice is carried out, not by special craftsmen but by the ordinary tenants (p.: dehqān) who also grow and harvest the rice, and therefore receive 1/5 of the crop. The 4/5 belonging to the owner of the land is normally sent straight to pāykōbtī, as the whole process of treatment is here called. The threshed paddy is first put to soak in a rectangular pit in the ground, the sides and bottom of which are covered with woven mats (p.: būrīā). The paddy is kept constantly wet by leading a stream through the pit. Close by, an "oven" (p.: dēgdān-i-shālī) is constructed, consisting of a pit in which a man sits and keeps a fire burning in a fireplace in one of the pit sides. From the fireplace a flue is dug to the surface where a large round-bottomed cauldron (p.: dēg) is placed. By the cauldron sits another man and ensures that the damp shālī is "roasted" for a few minutes, stirring it the while with a little iron spade (p.: bēlcha) similar to that used in Laghmān. Thereafter the paddy is pushed out of the cauldron by means of a special pad and laid to dry in the sun, before being sent to the stamp-mill (pāykōb or awjuāz). Here, according to my informant, it is milled for 2-3 hours until the grain is hulled, then cleaned in the winnowing trays, and finally returned for a further half-hour's milling. After describing the processing of lok-rice, I shall discuss more fully the significance of parboiling and the subsequent drying. Here it must suffice to say that the process described facilitates hulling and is considered peculiar to the ma’īn variety of rice. Cultivation and treatment of lok-rice in Lōgar. Lōgar lies southeast of Kābul and has a much more severe climate than Laghmān. It lies more than 1800 metres above sea-level, and the winters are hard, with 2-3 months of snow. The growing season is therefore short, and only the more hardy lok-rice succeeds here. The cultivation of the two varieties of rice follows much the same course, and I have not been able to discover other differences than that lok is always sown broadcast and is not planted out, as is always (?) the case with ma’īn. Before describing the hulling process in this area I shall give a brief description of the actual cultivation of lok (informant: 'Abd-ul 'Azīz Sultanī, an engineer, from Padkhwāb in Lōgar). Work in the fields begins at the end of April. The fields are ploughed in both directions 3, 4 or 5 times and are then levelled with a special earth-moving implement (p.: rākūl, cf. Fig. 14) 4). When the area is quite plane small ridges (p.: pulwān) are raised around the separate fields. They may be made with the rākūl, or with a draw-spade (p.: anja, cf. Fig. 15) 5), but an ordinary spade (p.: bēl) is most commonly used. Water is now led over the fields for the first time, and they are once more levelled, a drag-planker (p.: māla) being pulled by two oxen 5-6 times through the mud of the fields (Fig. 16) 6). On the last occasion a sower goes behind the māla, and broadcasts the pre-germinated rice, resulting in the seed being covered by a very thin layer of mud, stirred up in the water by the passage of the māla. Sowing should normally be finished by about 8th June (15th Jauzā), and for the next three months it is only necessary to ensure that the fields are continuously covered by water. For the last month before the harvest a watcher is constantly in the fields to drive away birds, while scarecrows are also used. About 7th September (15th Sunbula) watering finishes, and a fortnight later the harvesting begins, and is completed in the course of a further fortnight. Before the end of Mīzān (i. e. before 22nd October) the harvest is normally home. Harvesting is done with sickles by the tenants and sometimes by extra hired help. The harvested paddy is transported as quickly as possible to the threshing floor (p.: kherman-jā or jā-i-kherman), a nearby fallow, where the paddy is allowed to dry for some time. The most important feature of the threshing floor is that it should be as hard and as free from dust as possible. To achieve this the chosen place is trampled by oxen after being watered, while sometimes straw or chaff is mixed with the resultant mud. After it has dried out again the site is thoroughly swept. The actual threshing is carried out by driving 4, 5, 6, or 7 oxen or asses, or sometimes horses, tied together, in circles through the spread paddy. While in the Kunar valley, and doubtless also in Laghmān, the innermost of the threshing beasts is tethered to a central pole (cf. Fig. 3), in Lōgar the animals are caused to walk in a circle by the head of the innermost animal being turned sharply to one side, a rope being tied between the halter and a back leg (as is known from south Afghanistan) 7). After the treading out, the straw (p. kā-i-shālī) is separated from the actual shālī (the grain in hull), first by hand and later by pitching with wooden forks (p.: chārshākh), and finally with wooden winnowing shovels (p.: bēl-i-rāshi). Later the straw is threshed once more, and reduced to chaff, which is an excellent fodder when mixed with wheat and maize straw. Immediately after threshing the paddy is dried in the sun, in order to be hard enough to resist processing in the stamp-mill and at the same time more easily lose its hull. Different methods of hulling are used in accordance with which type of finished rice is required: 1) lf the fine white se-bāra (= three-times) rice is desired the paddy must go three times through the stamp-mill. After the first stamping about half of the hulls (p.: subūs) are loose, and they are removed by tossing (p.: bād kardan) with wooden shovels (p.: rāsh-bēl). The grains of rice, however, are still of a yellow-gray colour, on account of a thin membrane which still adheres to the grain. This half-cleaned product is the so-called jandalī rice, which is also produced by the method described under 2) below. A second and third stamping, however, removes this membrane and produces the prized se-bāra rice, which is undoubtedly our polished rice. Whatever hulls are left after the second and third stamping are removed by tossing, and the dust on the actual grain is removed by means of the winnowing-trays (p.: chaj). Finally the rice is sorted by size in three different sieves with holes of different size. 2) Very many ordinary villagers make do with jandalī rice, and for this the paddy can either be processed as described above, or else milled in a special light rotary quern, called jandalī. It resembles an ordinary rotary quern of stone (p.: destās or āsiā-i-dest), but it is made of baked clay. Its milling surface is roughened, either with small knobs or with incised grooves, and it is used in exactly the same way as a stone quern. It is common in Lōgar and apparently around Kābul itself, but is unknown in Wardak. Its extensive use in Lōgar is accounted for by the fact that many cultivators there do not have sufficient paddy to justify the use of the stamp-mill. Moreover, the jandalī-quern can be operated by women, while the stamp-mill requires trained men - even though in Lōgar these are ordinary tenants. Jandalī rice is also cheaper, and there is not so much wastage. Finally, if there is need for the fine white se-bāra, and one has a small portion of jandalī rice, the women will pound it in a stone mortar (p.: jawāz-i-destī), which is usually merely a hole in a large stone or in the rock, while the pestle is normally also of stone (p.: dest-i-jawāz). This mortar may also be used for the complete hulling process, but this only seldom is done in the Lōgar and Kābul area. In Vavilov's description of hulling in Herāt he mentions only the use of the hand mortar s8). Final remarks. Of the methods of processing rice here described, those used for the production of ma’īn rice are of especial interest. This is in particular due to the process involving the parboiling of the rice, a practice which is widespread in India. From the important rice district of Swāt in north Pakistan I have received the following information on rice processing in a letter from Bishop Jens Christensen in Mardan, Peshāwar District: "So far as I can discover there are two factors to be taken into consideration: a) there are various types of rice and they are variously processed, b) practices vary with the oldfashionedness and poverty of the practicer. In Swāt the majority of people now own a machine, and all the old methods have to a large degree lapsed. - In some places they use a large iron plate, heated over a fire, instead of the oldest method of using redhot sand. The reason for boiling the rice is to make it easier for people to prepare food speedily, for otherwise they would have to boil the rice very much longer at home. The idea behind the hot sand - or the iron plate - is to give the rice a slight colour, as well as to dry it out quickly. It is now almost impossible to find a stamp-mill, since modem methods have come into use." If one further takes into consideration that racially and culturally, as well as physically, Swāt bears a great resemblance to Laghmān 10), it would be reasonable to regard the processing of ma’īn rice in Laghmān as an oldfashioned but highly evolved practice, which has survived through its isolation from more modem influences. The production of parboiled rice in India is to a large extent mechanised, and is carried on by a number of different methods. The principle involved is that the paddy is soaked in water for a varying period, exposed briefly to boiling water or steam, and then dried in the sun or on artificially heated drying platforms 11), before being sent to the mechanical rice-mills. The period of soaking, and of boiling or steaming, varies with the type of rice being treated and with the temperature at which the rice is soaked. The normal process is to soak the paddy in large brick tanks for 1-3 days at a temperature of about 60-72° C, before exposing it, under pressure, to steam for 10-20 minutes 12). But despite mechanisation a very large proportion of lndia's rice is still processed by very simple methods in the villages. Here hulling is carried out first and foremost by means of pestle and mortar, though occasionally, particularly in north India, by means of a footpowered pivoted pestle (cf. p. 228); on the other hand, the stamp-mill is not recorded as used in the lndian sub-continent, and perhaps only occurs in the northwest 13). The paddy is normally dried in the sun, though also on hot iron plates and by mixing with hot sand 14). However, the information which I have from India is both too general and at the same time too compressed to allow a detailed comparison with the methods of processing ma’īn in Afghanistan 15). It is possible, however, to learn from India the effects of parboiling on the finished product. The advantages are in brief that the grain is toughened by a partial formation of starch, the hulls are more easily removed, and the grain is less likely to break; it is moreover well suited to the poorer qualities of rice, giving them better keeping qualities and making them less liable to insect attack. In addition, more vitamins and other nutritional values are preservedthroughout husking, washing and the final preparation for the table -than in the ordinary white rice 16). The main criticism of parboiled rice is directed against its colour and aroma, which do not appeal to people accustomed to ordinary white rice 17). The main conclusion is that parboiled rice is a much more valuable foodstuff than white rice. Within the rice-areas of the world parboiled rice is a specifically Indian phenomenon, and where it is produced outside India it is always with a view to export to India or to Indian or Indian-influenced populations elsewhere, for example the harbour-towns of the Red Sea. Thus parboiled rice is widely produced in Burma, but never consumed by the Burmese 21), while almost all the rice from British Guiana is parboiled 22). It may thus be regarded as certain that the parboiling of rice originated on the Indian peninsula, and it is probable that the practice is very ancient there. The reason for the development of this particular process is uncertain, but, as has been said, parboiling is particularly associated with certain varieties of rice and must have reached East Afghanistan together with these varieties, extending later, doubtless comparatively recently (50-70 years ago?), to Afghan Turkistan 23). The actual origin of the parboiling of rice must doubtless be looked for in the purely practical advantages during the husking process, and as people gradually accustomed themselves to this special form of rice the process assumed in course of time its present form. The convenience of the method is not without significance for its continued existence. It saves both time and fuel, while in addition the rice remains fresh after boiling for much longer than rice which has not been previously parboiled 24, 25). So far as I am aware, the process of soaking and parboiling is confined to definite Indian varieties of rice, and is not used in threshing and hulling other sorts of grain. Artificial drying to facilitate threshing has, or had, a widespread application, under other forms and for other types of cereals, in temperate climates, e. g. in the Faroe Islands, in northeastern Europe and perhaps in western Europe 26). But it is doubtful whether the artificial drying of paddy has any connection with these. The technique of using heated sand for drying and for a sort of roasting is more usual in India than has been suggested above, as it is used, inter alia, for making various types of "puffed corn" from rice 27). In Afghanistan, too, it is used more widely than recorded above. In the bazar in Kābul pop-corn is prepared by mixing maize with hot sand in large clay bowls, the sand being heated in a large box-shaped clay oven which in principle resembles closely the Laghmān ovens 28). Chick-peas (Cicer arietinum, p.: nakhūd) are similarly treated in the Kābul area by being mixed with hot sand, which is then, as in the case of the maize, sieved away in a wire-mesh sieve 29). The use of hot sand is undoubtedly old in India and Afghanistan, and is perhaps older than roasting on iron plates (cf. p. 226). The method is certainly used much more widely than here recorded. Finally with regard to the water-driven stamp-mill, this is found with small variations throughout the greater part of the rice-districts of Afghanistan 30), and in addition in Swāt, but it does not appear to occur in the remainder of the Indian sub-continent 31). On the other hand it is found in a belt right across Asia from the Mediterranean to China, and in this area is used above all for rice-hulling. In a developed form it is known from Tosya in central Anatolia, with a large 12-chambered driving wheel and with three stamping arms, of which two, with iron rings on the ends, are designed for hulling, while the third is used for polishing 32); in the Caucasus it is used by the Gurian tribe of Georgia, and in Persia only in Mazanderan (in both areas single-armed) 33). It is common in west Turkistan, and is also used here in the same form for the production of paper 34). Hedin records the stamp-mill in east Turkistan, and it is also found in south China, and according to a single record also in Japan. The south Chinese stamp-mill (Fig. 17) is driven by a large multi-chambered wheel and has four stamping arms, thus recalling the Anatolian stamp-mill 35). Outside these areas the stampmill is found in northern Indochina (according to Heine-Geldern as a result of Chinese influence 36) and it is finally known from Sumatra 37), where it appears to be an isolated occurrence, and must be regarded as the result of influences from south China (or Indochina) rather than from western India. While the water-driven stamp-mills hitherto mentioned have all been of practically the same construction and are largely used for the same purpose of rice-hulling, stamp-mills are known in Europe with many uses and of various constructions, but all based on the same principle, an undershot (or overshot) wheel directly fixed to an axle on which sit the tappets which transfer the drive. The first recorded stamp-mills in Europe are from the 11th century and throughout the Middle Ages they extend their area of use, until they finally disappear in the 19th century 38). These European stamp-mills were perhaps in their special development independent inventions, but the basic principle of the use of water-power goes back to the Classical period in the Mediterranean area. To this degree it would seem that there is a connection between the European stamp-mills and the rice-mills of Asia. For further consideration of the possible place of origin of the stamp-mill there are two factors to evaluate: the actual basic form from which it may have developed, and the knowledge of the use of water as a power source. There is a convincing possibility that the water-driven stamp-mill for rice has developed out of a single-armed foot-powered pivoted pestle. This apparatus, which in turn is derived from the simple pestle and mortar, was used over a wide area in the ancient world, all the way from Europe to the Far East. In somewhat varying forms it is known from Poland, Bohemia, Hungary, Austria, Yugoslavia (Krain) and ltaly 39), as well as from Trans-Caucasia 40), and from Persia, where it is clearly very extensively used. On the other hand it seems to be unknown in west Turkistan (perhaps supplanted by the actual stampmill). From east Turkistan there are no records of its use, but it is known from large parts of China where it is used for other purposes besides rice-hulling 42). Of the remainder of the Far East it occurs in Japan, western Tonkin, Cambodia and Siam 43), and finally in Indonesia (west and east Sumatra) 44). Whilst the pivoted pestle has presumably spread to Indochina from China proper, its occurrence in Sumatra is clearly the result of influence from India, as the pestle is here called by its Indian name 45). Within the Indian subcontinent the pivoted pestle is especially at home in the north, where it is in very general use 46), but it is also known from south India and from Burma 47). Finally in Afghanistan it is in use in many districts, partly for rice-hulling but also for crushing clay for the making of pottery 48). Thus the pivoted pestle is in much more widespread use than the stamp-mill, a circumstance which supports the theory that the stamp-mill was developed from the pivoted pestle. But another circumstance also appears - that within their range the two types of pestle seem to complement each other. Here it would he safest to restrict consideration to the areas where information is fullest, to Persia (less the Caspian provinces) and India, which possess the pivoted pestle, and to Afghanistan and west Turkistan, where the stamp-mill is dominant. This distribution may suggest that other factors (economic, physical, etc.) as well as the historical have controlled the spread of the pestle 49). It is otherwise difficult to explain the absence of the stamp-mill from the greater part of Persia, where the use of water-power in the form of the horizontal mill is well known. That the stamp-mill does not occur in India is perhaps more understandable, in view of the fact that the horizontal mill is also unknown there. As concerns chronology, we are ill provided with datum points. Concerning the pivoted pestle we only know that it existed in China as far back as the Han Dynasty (221 BC- 220 AD ) 50), while for the other areas our knowledge does not go back any appreciable distance. It should be recorded that, on a basis of distribution studies, Leser has drawn up a complex of agricultural implements, consisting of the four-sided plough, the two-piece flail, the rigid harrow and others, which occurs on the one hand in Europe and parts of the Near East, and on the other in large areas of Further India and the Far East. In this complex Leser also lists the pivoted pestle, and he considers that there is a historical connection between these two separate (?) distribution areas, without being able to state with certainty whether the complex originated in the west or the east; Leser believes, however, that the route travelled by the complex went south of the Himalaya, and he suggests that the direction followed was from the west 53). I find it impossible in the present discussion to take up a clear position with regard to all the components of Leser's complex, but in the particular case of the pivoted pestle I am most inclined to believe that it originated in Asia, in immediate association with the cultivation of rice. Turning to the stamp-mill, we find that its uniform design throughout the whole of its area of distribution is a strong indication of a historical relationship. But here too chronology fails us. In China illustrations of the stamp-mill are found at least around 1700 AD, doubtless also from the preceding Ming period, and possibly from as far back as the 12th century 52). From the other areas, with the exception of Europe, there is no information, but in Europe the stampmill is known from the 11th century onwards. It would thus seem that the stamp-mill, or at least its forerunners, occur earliest in the west. The knowledge of the use of waterpower in watermills is in China traditionally dated to the 3rd century AD, to which period is ascribed the invention of the water-mill by a certain Tu Yü 53), but despite this tradition it is most probable that the Chinese water-mill came into existence under influence from the west 54). It is generally considered that the water-mill with a horizontal driving-wheel originated in the latter half of the First Millennium BC somewhere in the mountain areas of the Near East, and that it spread thence both east and west 55). No exact date is known, but we know that the exploitation of water-power began in the last centuries before the Christian era to expand rapidly, and caused a technical revolution which reached its climax with Vitruvius's epoch-making watermill in which, instead of using the inefficient direct power transmission employed in horizontal mills and ordinary stamp-mills, he transferred power by means of a gear system from a vertical wheel (either under- or overshot) 56). It is possible to discuss which would appear to be the most primitive, the vertical undershot water-wheel (as used in the stamp-mill), or the horizontal wheel of the horizontal mill, but there is no doubt that, in the light of the information we at present possess the principles seem to be equally ancient, and that they can be traced to the latest centuries BC in the area of the Eastern Mediterranean and the Near East. But there are more points of agreement and association between the two types of mills than the purely chronological. I have several times referred to the striking similarity of design among stamp-mills wherever they occur. The same is true of the horizontal mill throughout its range, which, in addition to northwest Europe, covers an almost continuous area stretching from both sides of the Mediterranean, through the Near East, Persia, the Caucasus, Afghanistan, west and east Turkistan, as far as north China, while from Afghanistan it also extends eastward through northern India (in the Himalaya) into south Tibet, and finally ends in west China 57). In this area of distribution I consider that a very exact agreement can be seen with the distribution of the stamp-mill. I find particularly significant the non-appearance of the horizontal mill over the greater part of India, including the areas where the pivoted pestle occurs. I consider, therefore, that the possibility of a connection between these two types of mill should not be excluded, if for no other reason because of the idea of exploitation of water-power basic to both. The gap found in the distribution map of the stamp-mill between east Turkistan and south China will thus he filled when we remember that the horizontal mill is first and foremost designed for wheat, barley and the like, while the stamp-mill belongs predominantly to the rice areas. Whichever way the horizontal mill may have wandered from the west to east, the route taken by the stamp-mill lay through central Asia. Without being able to suggest a final location for the actual invention of the rice-stamp-mill I believe that it can he provisionnally stated that it arose at some point where the cultivation of rice with the use of the pivoted pestle met the horizontal mill. This may have happened in the course of the spread of rice to the west following the campaigns of Alexander, or it may, of course, also have occurred in China. If I were to pick one particular area I should consider a western or central Asiatic origin to be the most prohable, perhaps a point on the old trans-Asiatic caravan road, some time in the First Millennium AD. But I shall forsake the quaking ground of hypothesis. The main object of this article was to present new material and to compare with each other the two methods of processing rice in Afghanistan. I should like to take this opportunity of expressing my heartfelt thanks to Mr. Ahd-ul 'Azīz Sultanī for his invaluable help, and to Mr. Mohammad Hasan Kakar and Dr. A. Ghiās Sāfi, our kind hosts during our visit to Laghmān; and finally to record my profoundest gratitude to the Royal Afghan Government and its officials for their invaluable help to us during our work in Afghanistan. Klaus Ferdinand